Evolution and plasticity of morph‐specific integration in the bull‐headed dung beetle Onthophagus taurus - Rohner, Patrick T.; Macagno, Anna L. M.; Moczek, Armin P. (Ecology and evolution, 2020)
Developmental and evolutionary processes underlying phenotypic variation frequently target several traits simultaneously, thereby causing covariation, or integration, among phenotypes. While phenotypic integration can be neutral, correlational selection can drive adaptive covariation. Especially, the evolution and development of exaggerated secondary sexual traits may require the adjustment of other traits that support, compensate for, or otherwise function in a concerted manner. Although phenotypic integration is ubiquitous, the interplay between genetic, developmental, and ecological conditions in shaping integration and its evolution remains poorly understood. Here, we study the evolution and plasticity of trait integration in the bull‐headed dung beetle Onthophagus taurus which is characterized by the polyphenic expression of horned (‘major’) and hornless (‘minor’) male morphs. By comparing populations subject to divergent intensities of mate competition, we tested whether mating system shifts affect integration of traits predicted to function in a morph‐specific manner. We focussed on fore and hind tibia morphology as these appendages are used to stabilize major males during fights, and on wings, as they are thought to contribute to morph‐based differences in dispersal behavior. We found phenotypic integration between fore and hind tibia length and horn length that was stronger in major males, suggesting phenotypic plasticity in integration and potentially secondary sexual trait compensation. Similarly, we observed that fore tibia shape was also integrated with relative horn length. However, although we found population differentiation in wing and tibia shape and allometry, populations did not differ in integration. Lastly, we detected little evidence for morph differences in integration in either tibia or wing shape, although wing allometries differed between morphs. This contrasts with previous studies documenting intraspecific differentiation in morphology, behavior, and allometry as a response to varying levels of mate competition across O. taurus populations. We discuss how sexual selection may shape morph‐specific integration, compensation, and allometry across populations. We sought to further our understanding of how population divergence in the strength of sexual selection shapes morph‐specific trait integration and secondary sexual trait compensation across populations in a polyphenic dung beetle. We find evidence for integration between tibia shape and size with horn length, but little divergence among populations with diverging mating systems. We discuss how the strength of sexual selection shapes morph‐specific trait integration, secondary sexual trait compensation, and allometry across populations.